Seasonal distribution of cetaceans in the European Atlantic and Mediterranean waters - Virgili, Auriane; Araújo, Hélder; Astarloa Diaz, Amaia; Dorémus, Ghislain; García-Barón, Isabel; Eira, Catarina; Louzao Arsuaga, Maite; Laran, Sophie; Saavedra, Camilo; Van Canneyt, Olivier; Ridoux, Vincent (Frontiers in Marine Science, 2024)
As apex predators, cetaceans play an essential ecological role in marine ecosystems. Fluctuations in the abundance of these top predators linked to human activities can have detrimental consequences for the entire ecosystem. Cetaceans face numerous anthropogenic threats that can have both short and long-term effects. To ensure their conservation, it is necessary to identify changes in seasonal distributions at small and large scales. We aimed to model the seasonal distribution of the most abundant cetacean species in the European Atlantic waters and the Mediterranean Sea by assembling datasets collected over 16 years of surveys using a standardised line-transect protocol. Data were homogenised, detection functions fitted and effective strip widths estimated. We extracted environmental variables integrated over the water column, which we transformed using a principal component analysis (PCA). The dimensions of the PCA were then integrated as explanatory variables in a generalised additive model, taking seasonal and spatial effects into account to predict the seasonal cetacean distribution. We were able to highlight changes in the spatial distribution and/or density of cetaceans throughout the year at a large scale, considering environmental extrapolation areas to predict where environmental variables were sampled during the surveys. For minke (Balaenoptera acutorostrata) and fin (B. physalus) whales, densities varied over the seasons but not the distribution, suggesting a seasonal migration outside the survey areas. For common dolphins (Delphinus delphis), bottlenose dolphins (Tursiops truncatus) and harbour porpoises (Phocoena phocoena), densities varied little but distributions did over the seasons. Finally, pilot whales (Globicephala spp), Risso’s (Grampus griseus) and striped (Stenella coeruleoalba) dolphins showed little seasonal variation in their distribution. Using monthly dynamic environmental variables at depth and PCA dimensions in habitat models, we produced maps of the seasonal distribution of cetaceans in the Mediterranean Sea and the European Atlantic waters to help fill gaps in our knowledge of cetacean distribution.